Smart waste bin design with automatic waste sorting system, ergonomic, functional, aesthetic, and IoT-based integrated point system - Zulfahmi Noor; Jumatiah; Haura Nurhaliza; Aqila Khoirul Umam (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Creating trash bins that are comfortable to use and attractive, integrated, and capable of automatic waste separation is the answer to the waste problem that has become a major issue in Indonesia and even the world. The purpose of this study is to analyze and design smart and ergonomic trash bins. Methods: This study in Tanjung Redeb, Berau Regency, surveyed 184 trash bin users. Data were collected through observation, interviews, questionnaires, and literature review, validated with SPSS, and processed using the QFD method to design an integrated, user-friendly trash bin. Findings: The results obtained based on the interpretation of user requirement data show that users of trash bins want materials that are easy to clean with an improvement ratio of 1.25, have usage instructions with an improvement ratio of 1.0, are comfortable to use and practical with an improvement ratio of 1.0, have audio information with an improvement ratio of 1.0, use renewable and environmentally friendly energy with an improvement ratio of 1.25, flexible and lightweight with an improvement ratio of 1.0, discarded waste can be converted into points with an improvement ratio of 1.25, waste can be separated automatically with an improvement ratio of 1.0, integrated with waste management personnel (who know the volume of waste in real time with an improvement ratio of 1.0), and attractive trash bins ratio of 1.34. after collecting and reprocessing the data, the results show that smart trash bins are ergonomically designed, integrated with personnel and sorting systems to meet user satisfaction. Conclusion: Therefore, an ergonomic design for smart waste bins is needed based on the needs of waste bin users in Berau Regency. Unlike previous researchers who generally focused only on technological aspects and automatic selection. Novelty/Originality of this article: The originality of this research is also demonstrated through the development of a design that not only emphasizes technical functions but also aesthetic aspects, environmental sustainability, and increased community participation in sustainable waste management.